Restricting water withdrawals of the thermal power sector: An input-output analysis for the northeast of the United States. (10th October 2018) - Dilekli, Naci; Duchin, Faye; Cazcarro, Ignacio
Abstract: As water scarcity and pollution of sources become increasingly severe and widespread, competition over this resource intensifies. Unlike much of the rest of the world, thermal power plants in the US are the biggest users of water due to heavy reliance on once-through cooling technology. This cooling technology withdraws large amounts of water and discharges it back almost in its entirety but at higher temperatures. These water withdrawals are increasingly subjected to legislation intended to reduce the effects of thermal pollution. We utilize an interregional input-output model for quantifying the money costs and the shifts in the distribution of power production by state and by technology when withdrawals and discharges of fresh water are restricted. This model allows for the choice among alternative power generation technologies with different cost structures within each state. We analyze a Baseline scenario for 2010 and alternative scenarios that impose constraints on water withdrawals and inter-state power transmission. Based on an annual analysis, we conclude that this region can satisfy its electric power requirements while fully complying with legislated water restrictions at moderate cost by compensating the curtailment of output from some plants by otherwise unutilized capacities of other plants in the region. When we revisit the analysis using a monthly time step, however, sharp seasonal variations exhibit a strong impact on economic costs. In the summer months, intra-state transmission does not suffice, and regional demand cannot be met in the absence of substantial inter-state transmission. Highlights: An interregional input-output model is constructed for the Northeast of the US. Thermal power plants are large water users, mainly due to once-through cooling. Water withdrawals are subjected to legislation to reduce thermal pollution effects. We quantify cost and distribution of power production shifts with water constraints. Contrary to annual, monthly analysis show strong costs due to seasonal variability.